Goya in the Royal Academy of History: Analisys of art documentation - Nebreda Martín, Lara (Revista General de Información y Documentación, 2012)
Abstract: The main source of information regarding an art piece is always the piece itself. But there is also specific documentation created during the existence of an art piece, whose analysis truly fosters the development of any scientific research on any specific work of art. Starting from the study of the documentation generated by four portraits painted by Goya, now preserved at the Royal Academy of History, we present the most common sorts of documents created by works of art and we link their origin to the period of existence of the piece. We also set out the advantages of controlling and understanding these dossiers through the documentary reconstruction of each portrait, aiming to prove that documentation in Art is an interesting research topic that offers some results and helps to the development of other disciplines.